2020
DOI: 10.1177/0734242x20902835
|View full text |Cite
|
Sign up to set email alerts
|

Demolished concretes recycling by the use of pneumatic jigs

Abstract: Large quantities of construction and demolition waste is generated annually around the world. Part of this material is processed in recycling plants. After removing metals, fines and lights, the construction and demolition waste is crushed and sized and can be used as aggregates for low resistance concrete, for road sub-base, city landfill and other low value-added applications. For their use as coarse aggregate in structural concretes, construction and demolition waste must exhibit high densities and regulari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The jig presented three products: top layer (light particles), middle layer (mixture of light and dense particles), and bottom layer (denser particles). The results were published by Sampaio et al [30] and present the following results.…”
Section: Concentration In Water Jigssupporting
confidence: 54%
“…The jig presented three products: top layer (light particles), middle layer (mixture of light and dense particles), and bottom layer (denser particles). The results were published by Sampaio et al [30] and present the following results.…”
Section: Concentration In Water Jigssupporting
confidence: 54%
“…The compressive strength of EPUC is 58.5 MPa~61.2 MPa, while the average density is 1768.5 kg/m 3 and the average compressive strength is 59.7 MPa. By comparison, it is found that, while EPUC meets the strength level of C50 concrete, its density is only 70% [26]. The average compressive strength of the six groups of specimens was taken to draw the stress-strain curve, as shown in Figure 9.…”
Section: Mechanical Properties (1) Compression Propertiesmentioning
confidence: 99%
“…Hence, the operational and maintenance expenses associated with dust removal (alongside the necessary accessories for dry jigging systems) can become the most significant costs in a CDW recycling facility [113]. Secondly, the efficiency constraints associated with density separation in air (as discussed in Section 3) typically restrict the effectiveness of dry jigging when undertaking more precise processing tasks, such as separating recycled concretes based on their attached mortar content or their strength classes [123].…”
Section: Construction and Demolition Wastes (Cdw)mentioning
confidence: 99%